Thrombocytopenic thrombotic purpura related to COVID-19 vaccine: Apropos of 4 cases - Dos Santos, Célia (2024)
The global pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to vaccine deployment in record time.1 Very rare cases of thrombotic events associated with thrombocytopenia have only emerged after vaccination of millions of people.2 Acquired Thrombotic Thrombocytopenic Purpura (aTTP) is one of the adverse syndromes that has been progressively reported in the literature. This form of thrombotic microangiopathy (TMA) is associated with presence of autoantibodies against ADAMTS13,3 resulting in formation of platelet thrombi within the microcirculation. Case reports showed that several vaccines against SARS-CoV-2 triggered a de novo or relapse episode of aTTP as summarized by Buetler et al.4 Effective treatment needs to be provided as soon as possible to patients with TTP as it can be a fatal disease. Here, we describe four cases of a newly aTTP diagnosis who had received ChAdOx1 nCov-19, the heterologous recombinant adenovirus combination rAd26 and rAd5 (Gam-COVID-Vac, Sputnik-V) or the inactivated whole virus (BBIBP-CorV, Sinopharm) vaccines...